Evaluation of the detection errors of heat focus estimated by the GOES Imager Sensor - Silva, Viviane Valeria da; Pereira, Gabriel; Cardozo, Francielle da Silva (Geosaberes, 2019)
The negative impacts on the environment caused by fires represent one of the greatest environmental challenges of our time. The demand for products with greater accuracy in fire characterization and behavior has increased significantly in recent decades. In this regard, in relation to the importance of the systematization of fire products, as well as their significant use, the limitations related to the accuracy of information need to be remedied. The main objective of this work was to analyze the accuracy of the information contained in the product WFABBA / GOES, of heat focus detection. It was found that overestimation of the outbreaks in all the years of the analyzed series suggests that this result can be based on other research regarding the relationship between the errors found and their impacts on the emission inventories of gases and aerosols from biomass burning.